Stress Transfer and Matrix-Cohesive Fracture Mechanism in Microfibrillated Cellulose-Gelatin Nanocomposite Films - Melo-Hurtado, F; Caballero-Alvial, L (Elsevier Ltd, 2018)
Microfibrillated cellulose (MFC) obtained from eucalyptus was embedded in gelatin from two sources; namely bovine and salmon gelatin. Raman spectroscopy revealed that stress is transferred more efficiently from bovine gelatin to the MFC when compared to salmon gelatin. Young s modulus, tensile strength, strain at failure and work of fracture of the nanocomposite films were improved by ∼67, 131, 43 y 243% respectively when using salmon gelatin as matrix material instead of bovine gelatin. Imaging of the tensile fracture surface of the MFC-gelatin nanocomposites revealed that crack formation occurs predominantly within bovine and salmon gelatin matrices rather than within the MFC or at the MFC/gelatin interface. This suggests that the mechanical failure mechanism in these nanocomposite materials is predominantly governed by a matrix-cohesive fracture mechanism. Both strength and flexibility are desirable properties for composite coatings made from gelatin-based materials, and so the findings of this study could assist in their utilization in the food and pharmaceutical industry. © 2018 Elsevier Ltd